Synchronization of oestrus and artificial insemination or natural mating in kids 6-7 months old - ΚΑΡΑΤΖΑΣ, Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In a herd of 92 Zaanen seminproved kids, 6-7 months old, was performed synchronisation of oestrus with sponges (Veramix Upjohn 60 mg MAP). The sponges were maintained in the kids vagina for 19 days. Two days before the withdrawal of progestagen an intramuscularly injection of 500 IU PMSG had been given to all kids. Forty kids inseminated twice with selected frozen semen, in pailletés of 0.25 ml. The first insemination took place 32 hours after the withdrwal of sponges and the second one 22 hours after the first one. In each insemination we used a pailleté contained 220-250 X 106 spçrmatozoaria. Thirty six kids of the remaining were separated in to six groups. A fertile buck was placed to each group. The groups were maintained in separated spaceous pens. After the first oestrus the kids who had been inseminated artificially incorporated with the groups of natural mating. At the second and third oestrus the matings had been done naturally. The fertility percentages at the first oestru after the withdrawal of progestagen by natural mating and artificial insemination were. 27.77% and 30% respectively. By natural mating at second and third oestrus the corresponding percentages were 46.3% and 65.5% respectively. The low fertility percentage at the first oestrus may be caused by the influence of the small age of the kids, that the number of kids who showed oestrus without ovulation was increased. Thirty four of 40 kids, a proportion of 85%, that were inseminated artificially showed intensive vaginal signals of oestrus and only 4(10%) showed light ones. Two kids showed no signals of oestrus at all. Although the fertility percentage in this age after synchronization and artificial insemination was low, it is suggested to be done because this thechnique may be acted as a trigger for the further good reproductive ability. In this herd 73,3% lambed normally and relatively early